Acoustics of nanodispersed magnetic fluids - Polunin, V. M. (Vi͡acheslav Mikhaĭlovich) (CRC Press, 2015)
Acoustics of Nanodispersed Magnetic Fluids presents key information on the acoustic properties of magnetic fluids. The book is based on research carried out by the author as well as on many publications in both the Russian and foreign scientific literature from 1969 onwards. It describes a wide variety of topics, which together lay the foundation of a new scientific research area: the acoustics of nanodispersed media. The book examines the nanoscale structure of matter in specific areas and discusses the following:Model theory and known features of the propagation of sound waves in magnetised f.